The Work of Maternity and Infant Welfare Centres - Labour Party (Great Britain). Advisory Committee on Public Health
1926-01 1926 1920s 7 pages Private and Confidential. January, 1926. No. 121b. TRADES UNION CONGRESS. LABOUR PARTY. JOINT RESEARCH AND INFORMATION DEPARTMENT. ADVISORY COMMITTEE ON PUBLIC HEALTH. Achievements of the State in Health Services. THE WORK OF MATERNITY AND INFANT WELFARE CENTRES. The function of the Infant Welfare Centre is the education of the Mother in all that belongs to the health of the baby and the young child. Its chief aim, therefore, is to do preventive medical work. The knowledge that the well-to-do mother can easily obtain through education and reading, and the advice of the family doctor, is thus brought within the reach of all her poorer sisters. By weekly consultations with doctor and Superintendent or Health Visitor, and weekly weighings, the condition of the infant can be noted and errors in diet corrected; and by constant lecture-talks on such subjects as:- importance of breast-feeding, value of fresh air and sunlight, model clothing for infants, how to note early symptoms of illness, home-nursing and general hygiene - and with sometimes practical courses in cooking and needlework - the women are encouraged in habits of good motherhood. Most centres include in their activities the sale of dried milks, chemical foods, Malt and Oil, etc., at reduced rates and as ordered by the doctor, and some boroughs manage their free distribution of dried milk through the Centres. While most centres pass on cases of illness to hospitals, a very few arrange for definite treatment of disease, or of minor ailments; some have dental clinics attached or provide for dental work. Each centre may vary slightly in details of work and organisation, but the first aim of all is to teach. 292/824/1/135